Napusteni grad - Piekorz, Magdalena (Croatia : Factum, 2002)
A film about the life of the Italian minority in Croatia (and former Yugoslavia) told through the story of Piemonte (Zavrsje), an almost completely abandoned and ruined town in Istria. Gigi was among the rare ones who stayed in the town when Tito's Yugoslavia demanded that the Italian minority choose between the two homelands. Today, some 50 years later he's still the only "citizen" of the abandoned town.
Duration: 00:18:00
Keywords: Documentary films